PENDEKATAN SAINS TEKNOLOGI MASYARAKAT TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII - Indah Prawesthy Suteja; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
This research aims to know the existence of influence applying STM to class VIII SMP Trisula Salam Magelang student learning outcomes in the subject chemistry material. This population research is all class VIII, SMP Trisula Salam. Sampling technique used is population research. Research conducted by giving treatment in the form of applying of method study STM approach continued with post-test. Pursuant to result of research, obtained by mean assess post-test experiment class 100 and control class 80. Value of post-test experiment class and control class have the normal distribution and have same variants, while difference test two means ofÂ  t_count =2,725 with p=0,009. The result learning outcomes of experiment class is better than control class. Pursuant to result of research can be concluded that there is an influence of the method with STM approach to student learning outcomes of class VIII SMP Trisula Salam Magelang at the subject chemistry material.